Model Sosialisasi Nilai-Nilai Peduli Sosial dalam Kehidupan Bermasyarakat dengan Menggunakan Strategi Physical Self Assesment Kombinasi Answer Gallery pada Karang Taruna Desa Pakis Kelurahan Boto Kecamatan Wonosari Kabupaten Klaten Tahun 2016 - Arumsari, Anissa; , Dr. Ahmad Muhibbin, M.Si (2017)
This purpose of this research are: (1) to describe the model of socialization of the social care in the society using strategies Physical Self Assessment combinations Answer Gallery at Pakis village, Boto, Wonosari, Klaten district in 2016 (2) to knew about the implementation model of socialization of the care of the existing social held at Pakis village, Boto, Wonosari, Klaten district in 2016 (3) to difficulties in socializing values social care strategy Physical Self Assessment combination Answers Gallery in Desa Pakis, village Boto, Kecamatan Wonosari, Klaten district in 2016 (4) to well as solutions to overcome the constraints in the model of socialization values of social care by using the strategy of Physical Self Assessment combination Answers Gallery at Pakis village, Boto, Wonosari, Klaten district in 2016. The data were collected through informant, places and events ongoing socialization model of social care values in youth. The data collection techniques by using the method of observation, interviews and questionnaires. The data were analyzed using descriptive and inferential. This socialization models consist of planning, implementation testing, evaluation, improvement and refinement of the model. The resulting increase in pre-trial is 102.13, or 72.95% after the trial test model I rose to 122.07, or 87.19%, and after the trial resumed on models II score was increased to 132.93 or 94.95%. So the conclusion of the first trial to trial II increased 7.76%.